Portfolio that Constitutes Risk-Free Investments for Purposes of Effective Pension Planning and Management in Ghana - Stephen Delle Donpaala (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Ghanaians' everyday decisions are intricately linked to the concept of planning. When they need some kind of assistance, it seems reasonable that people would make choices based on what they believe would best serve their interest. This assertion has sparked a variety of hedging techniques, such as complete life insurance packages and insurance policies. All of the packages share the retirement package scheme, also called the Pension Scheme. The Scheme, among other things seeks to provide for Ghanaians' needs during their retirement years when they are unable to engage in active public service. Even though the Ghanaian employee seems to get selfless support from the system, there have been reported cases of bad management practices, fraudulent acts, unfair remuneration, and employee-employer conflicts. Sometimes people work all of their productive years and then retire with pay that was below what they had anticipated. This has led a number of unions organizations to plan a number of industrial actions in an attempt to grab the government's and the administration's attention. In this work, we'll look at how the addition of two required and one voluntary private pillar to Ghana's pension system has drastically transformed the country's present social insurance program. Even though private pensions were meant to be instruments for granting individual citizens autonomy and choice over their retirement decisions. The paper adopted a qualitative methodological approach and the analysis of results shows that the design of the Ghanaian three-tier scheme has a number of risks and institutional flaws that could jeopardize the elderly's ability to maintain a standard of living. Therefore, it argues for the need to reform the new scheme by (a) establishing statutory pension benefit insurance, (b) decreasing the number of pension service providers, (c) limiting the amount of money each pension service provider can spend on administrative issues, and (d) reducing the amount of money each pension service provider can spend on non-profiting projects and other risky investments or gambling options.